(untitled) (Journal of Engineering, 2026)
Time and cost overruns are problems that persist in projects involving transportation infrastructure, especially in developing regions. This research examines the empirical relationship between time inflation (TI), which is defined as the percentage increase in project duration from the original schedule, and financial inflation (FI), which is defined as the percentage increase in project cost from the original budget for road and bridge projects in Iraq. The problem that the research aims to cover is the escalation in project costs associated with time inflation, with the aim of quantifying this relationship to aid in project planning and risk management. Using a quantitative method, data from 18 completed projects were analyzed using descriptive statistics, Spearman’s rank correlation (ρ), and simple linear regression. The results show a very strong positive monotonic relationship between TI and FI (ρ = 0.743, p < 0.01). Regression analysis shows that the TI variable can explain about 32.9% variance in the FI variable (R2 = 0.329), and 1% increase in the TI variable can lead to an average increase of 0.556% in the FI variable. The study concludes that although time inflations are a significant cause of financial inflation in Iraqi road and bridge projects, there are other factors that have a significant influence on financial outcomes. These findings highlight the need for proactive schedule control as a basic cost-control strategy and suggest improved contractual and monitoring structures to reduce the financial consequences of delays.